Counseling on Efforts to Prevent Juvenile Delinquency to Create a Better and More Qualified Young Generation in Jaya Mulya Village, Kroya District, Indramayu Regency - Tasiroh; Didik Himmawan; Zuhrah Alraji; Dini Safitri; Tedy Sutrisno (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
Adolescence is a relatively vulnerable transitional age. They often exhibit certain behaviors. In addition to being vulnerable, adolescence is known as a period that makes them very unstable, uncertain and very easily influenced by their surroundings. Moreover, with the development of technology and the increasingly open flow of information, in addition to having a positive impact on adolescents, both in the fields of economics, science, and social and cultural fields. But it also has a negative impact. The activities carried out aim to provide understanding and awareness to adolescents or the younger generation about efforts to prevent juvenile delinquency and how to handle it so as not to fall into behavior that leads to crime. After gaining this understanding, it is hoped that adolescents and the younger generation can spread it to the environment around their homes or to friends in their social circles and increase parental vigilance in supervising their children. The delivery method used is in the form of counseling to the youth organization and the Jayamulya Village community, especially teenagers in Jayamulya Village about the prevention of juvenile delinquency.